The Impact of Practitioners' Personality Traits on Their Level of Systems-Thinking Skills Preferences. Issue 3 (3rd July 2021) - Nagahi, Morteza; Jaradat, Raed; Goerger, Simon R.; Hamilton, Michael; Buchanan, Randy K.; Abutabenjeh, Sawsan; Ma, Junfeng
Abstract: In this study, we used a structural equation modeling method to investigate the relationship between systems engineers and engineering managers' Systems-Thinking (ST) skills preferences and their Personality Traits (PTs) in the domain of complex system problems. As organizations operate in more and more turbulent and complex environments, it has become increasingly important to assess the ST skills preferences and PTs of engineers. The current literature lacks studies related to the impact of systems engineers and engineering managers' PTs on their ST skills preferences, and this study aims to address this gap. A total of 99 engineering managers and 104 systems engineers provided the data to test four hypotheses posed in this study. The results show that the PTs of systems engineers and engineering managers have a positive impact on their level of ST skills preferences and that the education level, the current occupation type, and the managerial experience of the systems engineers and engineering managers moderate the main relationship in the study.